Public school management in educational districts: The school manager’s challenges and attributions (Research, Society and Development, 2021)
This research had as its object of study the educational districts, which represent a teaching organization model used by some municipalities to strengthen ties and make the relationship between school and the Municipal Department of Education efficient. The main objective of the study was to analyze public school’s management in the municipal education network of Quixadá, Ceará, from the educational districts, as well as to discuss the role attributed to district directors and coordinators. As a methodological procedure, the qualitative research delimited in the case study was used. For data collection, observation, semi-structured interviews and document analysis were used. At first, the conceptual aspects that characterize public school’s management and the organization of teaching were sought through a literature review. In a second moment, the organization and management of educational districts in Quixadá were analyzed, seeking to understand how the management of schools happens and what the attributions of school managers are. The survey results indicate that management in educational districts centralizes the role of the school principal, further bureaucratizes the school administrative system, focus on the SME functions that should be performed by schools, such as the elaboration of the PPP and it diminishes the autonomy of schools. It is concluded that management in Educational Districts is incompatible with the principles of democratic and participatory management because it centralizes school management in the SME, which consequently reduces the autonomy of educational institutions.